Developing Artsteps-based Song Media to Make It Easier for Madrasah Ibtidaiyyah Students to Memorize Arabic - Namiratuz Zahra; Putri Yanuarita Sutikno (MAGISTRA: Media Pengembangan Ilmu Pendidikan Dasar dan Keislaman, 2025)
Arabic language learning in Islamic Elementary Schools (MI) still faces various obstacles in improving students’ abilities, especially in memorizing vocabulary. This condition demands innovation in learning media that effectively supports the Arabic memorization process. This study aims to develop Artsteps-based song media to facilitate MI students’ memorization of Arabic. This study uses the Research and Development (R&D) method, which includes the stages of analysis, design, development, implementation, and evaluation. The development of learning media is designed to combine audio song elements and videos on the Artsteps platform for a fun, contextual learning experience. The study’s results indicate that validation rates of 92.75% by material experts and 92.33% by media experts are suitable for use. In addition, the pretest and posttest data yielded an average n-Gain of 0.76 in the high category. Therefore, based on the study’s results, it can be concluded that the development of Artsteps-based song media is effective in facilitating MI students’ memorization of Arabic.